If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+3(y-4)=-3y
We move all terms to the left:
6+3(y-4)-(-3y)=0
We multiply parentheses
3y-(-3y)-12+6=0
We get rid of parentheses
3y+3y-12+6=0
We add all the numbers together, and all the variables
6y-6=0
We move all terms containing y to the left, all other terms to the right
6y=6
y=6/6
y=1
| 1/2n+3=4 | | 3=2y+1 | | (-8x+5)(-2-3x)=0 | | x+3/4=1/8 | | -0,5q^2+6q+12,5=0 | | 0.2n+9=7(0.4n-1) | | 12x+9=-27 | | 7(2n=3) | | 20y=2y-1 | | 7.1-2x=6.1 | | 2x-6+-5x=3(-x+7) | | 11.97+x=5x-0.11 | | 7+3(x=2= | | 0.23x-4.2=0.55x+7.2-x | | .5x-3=6 | | v+7/8=-1/2 | | 3m+3=15m= | | 2x+18=51 | | 1/4z-9=1 | | u+3.9=9.11 | | x+1/4=-5/8 | | 45=3w+12 | | 6x+100x=18*50 | | 2n12=82 | | =32−2u | | 2^(2x)=1000 | | 1000=2^2x | | x=x+19 | | 1m-1/4=-1/3 | | 1(-5y+8)=2 | | x+1/2x+11=2x+1 | | u-4.84=8.94 |